Governing Religion In Indonesia and France: Scope and Limits - Asep Saepudin Jahar (Ulumuna, 2018)
This paper discusses the complex implementation of an ideal framework for governing religion in Indonesia and France. Every country is required to apply a balanced approach to protect internal interests on one hand and adapting to the world’s values on the other. In practice, however, it is never possible to achieve such an approach perfectly. By investigating the existing rules on religion and civil rights in Indonesia and France, this paper argues that minority groups in both countries have not been treated justly with respect to their religion. Using the case of Ahmadis in Indonesia and Muslims in France, the paper explains how both countries face formidable challenges in maintaining the balance between an internal policy of harmony and peace, and securing civic rights in accordance with international values. In sum, France and Indonesia share a similar dilemma in attempting to ensure that religious and civil rights are neutral and objective for all people. In such matters, limitations are unavoidable.